Analysis of the Influence of Perceived Benefits, Easiness and Risk on Students’ Interest in Using QRIS - Muhammad Zhilalul Haq; Luqman Hakim Handoko; Asgaft Asysyad Rasyid (UIN Sunan Kalijaga Yogyakarta, 2023)
Research Aims: This research aims to examine the influence of the perceived benefits, easiness, and risks toward students’ interest in using QRIS among STEI SEBI students. Methodology: This type of research uses descriptive quantitative methods by collecting data through questionnaires and literature. The data obtained is then managed using the SEM-PLS (Structural Equation Modeling-Partial Least Square) tool with the SmartPLS version 4 application which goes through inner model and outer model tests. Research Findings: The results of this study indicate that the perceived usefulness have a positive and significant effect on the intention to use QRIS, the perceived ease of use has a positive and significant effect on the intention to use QRIS, and the perceived risk has a positive and significant effect on the intention to use QRIS. Theoretical Contribution: There have been many studies on interest in using QRIS. However, since this study focused on students’ interest will enrich and strengthen the existing theory. Research limitation and implication: This study limited to student of STEI SEBI. Consequently, the result might be differed with others and biased. Therefore, the future research should enhance the object of study and the variables.